Management of School-Parent Partnerships in Enhancing Student Learning Independence in Elementary Schools - Setiani, Erna Erawati (CV. Media Digital Publikasi Indonesia, 2026)
This study investigates the management of school-parent partnerships aimed at enhancing learning independence among elementary school students in two public schools in Cianjur, Indonesia: SDN Ibu Dewi 1 and SDN Cibulakan. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis to explore the planning, implementation, and evaluation phases of partnership management, along with enabling and hindering factors. The findings reveal that structured partnership management involving effective communication, active parental involvement, and collaboration with external stakeholders significantly supports students' learning independence. Differences between schools highlight the role of technology access and resource allocation in partnership effectiveness. Recommendations focus on strengthening planning, communication, and participatory programs to sustain partnership benefits. This study contributes to educational management literature by integrating theoretical frameworks with practical insights into fostering effective school-parent collaborations.